The effects of cognitive leisure activities on frailty transitions in older adults in China: a CHARLS-Based longitudinal study - Kai Sheng; Hao Chen; Xianguo Qu (BMC, 2024)
Summary Background In an effort to identify factors associated with frailty transitions that trigger a significant difference in preventing and postponing the progression of frailty, questions regarding the role of cognitive leisure activities on various aspects of older adults' health were raised. However, the relationship between cognitive leisure activities and frailty transitions has rarely been studied. Methods A total of 5367 older Chinese adults aged over 60 years from the China Health and Retirement Longitudinal Study (CHARLS) were selected as participants. The 2nd wave of the CHARLS in 2013 was selected as the baseline, and sociodemographic and health-related status baseline data were collected. The FRAIL Scale was used to measure frailty, while cognitive leisure activities were measured by the Cognitive Leisure Activity Index (CLAI) scores, which consisted of playing mahjong or cards, stock investment, and using the internet. After two years of follow-up, frailty transition from baseline was assessed at the 3rd wave of the CHARLS in 2015. Ordinal logistic regression analysis was used to examine the relationship between cognitive leisure activities and frailty transitions. Results During the two-year follow-up of 5367 participants, the prevalence of frailty that improved, remained the same and worsened was 17.8% (957/5367), 57.5% (3084/5367) and 24.7% (1326/5367), respectively. Among all participants, 79.7% (4276/5367), 19.6% (1054/5367), and 0.7% (37/5367) had CLAI scores of 0, 1, and 2 to 3, respectively. In the univariate analysis, there was a statistically significant association between a score of 2 to 3 on the Cognitive Leisure Activity Index and frailty transitions (odds ratio [OR] = 1.93, 95% CI 0.03 to 1.29, p = .04), while all other covariates were not significantly different across the three groups. After adjusting for covariates, participants with more cognitive leisure activities had a higher risk of frailty improvement than those without cognitive leisure activities (odds ratio [OR] = 1.99, 95% CI 1.05 to 3.76, p = .04). Conclusions Cognitive leisure activities were positively associated with the risk of frailty improvement in older adults, mainly when participating in multiple such activities. Older adults may be encouraged to participate in a wide variety of cognitive leisure activities to promote healthy aging.